2017
DOI: 10.1007/s10900-017-0382-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Clinic Absenteeism: A Novel Method of Examining Distance from Clinic and Transportation

Abstract: Delayed treatment and non-adherence are associated with inferior prostate cancer (CaP) outcomes. Missed clinic appointments (MA) are one form of non-adherence that may be preventable. We conducted a retrospective cohort study of 1341 scheduled clinic encounters for men referred to an academic urology clinic for evaluation of known or suspected CaP. Driving distance and public transit times were calculated using a Google Distance Matrix API algorithm. Zip code level data regarding socioeconomic status was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
3
18
0
1
Order By: Relevance
“…indicating that past no-show behavior is carried onto future appointments, as observed in previous studies [3,24]. Likewise, the number of no-shows in consultations in the previous year was found statistically signi cant and positively associated to no-show in previous works [13,15,25].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…indicating that past no-show behavior is carried onto future appointments, as observed in previous studies [3,24]. Likewise, the number of no-shows in consultations in the previous year was found statistically signi cant and positively associated to no-show in previous works [13,15,25].…”
Section: Discussionsupporting
confidence: 79%
“…There is consensus in the literature regarding the non-random nature of no-shows, and research has been published proposing statistical analyses of factors that may impact no-show rates [6,7]. Previous studies have shown that factors associated with no-show include patients' sociodemographic conditions such as age [4]; gender [7,8]; distance between home and healthcare unit [9,10]; race [11]; marital status [12,13]; level of schooling [14]; appointment characteristics -time [2], day of the week [9], and month [15]; elapsed time between appointment request and actual consultation [2]; and patient's clinical diagnosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…While distance to care is a potential barrier restricting access, data evaluating the association between distance and compliance with cancer screening are limited. ough our study is the first to analyze the association between distance and PC in the developing world, few studies addressed this issue in the US [4,[14][15][16]. One single-center study examined the association between distance and missed clinic appointments among men suspected of or being treated for PC [14].…”
Section: Discussionmentioning
confidence: 99%
“…ough our study is the first to analyze the association between distance and PC in the developing world, few studies addressed this issue in the US [4,[14][15][16]. One single-center study examined the association between distance and missed clinic appointments among men suspected of or being treated for PC [14]. Among 1,341 scheduled clinic encounters for 576 patients, greater distance was associated with improved compliance (compliant median � 11.8 mi vs. missed appointment � 10.4 mi, P � 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…The direct distance of 30 km from home to the hospital was the best cut-off point for participating in OCR. As geocoding, which provides geographical coordinates corresponding to a location on the earth, becomes easier to calculate [6], in the present study, we performed geographical analysis using this geocoding to investigate the impact of the distance from home to the hospital on participation in OCR. Subgroup analysis was performed according to a variety of clinical backgrounds.…”
Section: Introductionmentioning
confidence: 99%